Chemical characterization of a variety of cold-pressed gourmet oils available on the Brazilian market - Cicero, Nicola; Albergamo, Ambrogina; Salvo, Andrea; Bua, Giuseppe Daniel; Bartolomeo, Giovanni; Mangano, Valentina; Rotondo, Archimede; Di Stefano, Vita; Di Bella, Giuseppa; Dugo, Giacomo (Food research international, 2018)
Different specialty extra virgin oils, produced by cold-pressing fruits/nuts (olive, pequi, palm, avocado, coconut, macadamia and Brazil nut) and seeds (grapeseed and canola), and retailed in the Brazilian region of Minas Gerais, were chemically characterized. Specifically, for each type of oil, the fatty acid composition was elucidated by GC-FID, the contents of selected polyphenols and squalene were determined respectively by UHPLC-MS and UHPLC-PDA, whereas minerals were explored by means of ICP-MS. Olive oil was confirmed to have the highest MUFA content due to a valuable level of oleic acid, while oils from grapeseed, Brazil nut and canola were marked by nutritionally important PUFA levels. The highest SFA content found in coconut oil was mainly due to the high levels of lauric acid, known for its advantageous HDL-raising effects. As for polyphenols, gourmet oils from palm, coconut and canola showed higher levels of phenolic acids (e.g. p-hydroxybenzoic, ferulic, syringic, acids) than olive oil, which was though characterized by peculiar antioxidants, such as tyrosol and hydroxytyrosol. Also, olive oil had the highest amount of squalene, followed by the oil from Brazil nut. Finally, all the investigated oils had very low levels (order of μg/kg) of pro-oxidant elements, such as Cu, Fe and Mn. Overall, these findings may fill the gaps still present in literature on certain compositional aspects of commercially available gourmet oils. [Display omitted] •Specialty extra virgin oils are increasingly appreciated in the oil scenery.•Nine cold pressed extra virgin oils from nuts, fruits, and seeds were considered.•Different compositional traits were investigated by highly performing instruments.•Minor oil chemistry was deepened and possible effects of cold processing were argued.•The present study may be of practical relevance to oil consumers.